Haemodynamic and hormonal effects of captopril in primary pulmonary hypertension. - Ikram, H (1982)
The treatment of primary pulmonary hypertension is unsatisfactory. Since, in animals, experimental pulmonary vasoconstriction may be mediated in part by angiotensin II, we treated five primary pulmonary hypertensive patients with captopril for four days. To ensure accuracy of haemodynamic and hormone data, the patients were studied under conditions of constant body posture, regulated dietary sodium and potassium intake, and unchanged diuretic therapy. Captopril reduced mean pulmonary arterial pressure in parallel with plasma angiotensin II levels. Right ventricular ejection fraction recordings increased considerably in three of four patients. Systemic arterial pressure fell, but there was no change in right atrial pressure, cardiac output, or heart rate. The decline in plasma (and urine) aldosterone levels presumably contributed to the positive cumulative potassium balance and the rise in plasma potassium (mean 0.7 mmol/1). These encouraging results suggest that converting enzyme inhibitors warrant a formal trial with prolonged follow up in the treatment of primary pulmonary hypertension.